The effects of perceived nepotism and job stress on organizational citizenship behavior : an empirical study in Kyrgyz family-managed company - Kyzy, Djulietta Mahamatjan (My University, 2011)
Anahtar kelimelerNepotizm, İş stresi, OCB, Kırgızistan ÖZET Bu tez, Kırgızistan’da gıda ve içecek üreten Shoro aile şirketinde nepotizmin iş stresi ile örgütsel davranış üzerindeki etkilerini ölçen araştırmadan elde edilen verileri analiz etmek için yapılmıştır. Post-Sovyet devri işletmelere, özellikle aile işletmelerine, eskiden komünist rejimi tarafından kısıtlanan birçok yeni eğilimler getirdi. Uzun süre büyüyen aile işletmeleri şimdilerde ikinci neslin omuzlarında, bu yüzden nepotist davranış işletmenin ayrılmaz bir parçası haline gelmiş. Bu koşullarda, örgütsel vatandaşlık davranışın (bundan sonra OCB kısaltması kullanılacak) üzerinde nepotizmin etkisi yanlış analiz edilebilir. Başka ülkelerde nepotizmin OCB üzerinde etkisi araştırılmış ve negatif etki görülmüştür. Ama Kırgız şirketlerde bunun aynısı görülmeye bilir. Bu yüzden gerçek durumu göstermek için modele örgütsel davranışı negatif etkileyen iş stresini eklememiz gerekir. Ve bundan sonra nepotizmin gerçek yüzü incelenebilir. KeywordsNepotism, Job Stress, OCB, Kyrgyzstan

This paper was conducted in order to analyze data obtained from an empirical research study which investigated the effect of perceived nepotism on organizational citizenship behavior through job stress in context of Kyrgyz family owned group of food and beverage companies Shoro. Post-Soviet situation brought to business management new tendencies especially family-managed businesses which were restricted in communistic regime. For a long period family run businesses were growing and nowadays they are in arms of second generation, so nepotistic behavior became a real part of management. In these conditions the effect of perceived nepotism on organizational citizenship behavior (here and after used in abbreviation OCB) could be analyzed wrongly. In other countries effect of perceived nepotism on OCB was measured and showed negative relationship, while in Kyrgyz companies you can face to surprises, so to show real case there must be added disturbing element like job stress, which is negative and decreases OCB. So the real face of perceived nepotism can be shown through this examining.
Keywords: İş Stresi; İş Stresi_Kırgızistan; Nepotizm